Strategy of Maintaining Customer Loyalty (PT. Cipta Griya Dewata Case Study) - Diantini Suwena; Ni Putu Nina Eka Lestari (Enrichment : Journal of Management, 2021)
This study aims to analyze and find out what strategies are carried out at PT Cipta Griya Dewata in maintaining customer loyalty during the Covid-19 pandemic. The research method used is qualitative research methods. The informants in this study were managers and consumers from PT Cipta Griya Dewata who were taken by purposive sampling technique. Data analysis in this study used data triangulation by analyzing the results of observations, interviews, and documentation obtained from the study. The results of the study stated that in terms of SWOT, the strengths of PT. Cipta Griya Dewata includes enthusiasm, hospitality and good communication. The disadvantages include the lack of responsiveness of staff. The opportunities are broader marketing. The threat of increasingly fierce trade competition. Meanwhile, in terms of the Customer Relationship Management Strategy, companies are required to be consumer-centered, must understand the profile of consumers to understand more deeply the character of their consumers. Operational Customer Relationship Management that uses software has not been applied at PT. Cipta Griya Dewata. Analytical Customer Relationship Management is concerned with capturing, storing, extracting, integrating, processing, interpreting, distributing, using and reporting customer-related data to increase customer value and the company has been well done by PT. Cipta Griya Dewata